ANALISIS STRATEGI KOMUNIKASI GURU PAI DALAM MENGEDUKASI ORANG TUA TENTANG PARENTING ISLLAMI DI SMP TAQ Al HAMIDIYYAH BATEALIT - Azkal Nufus; Mufid (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study analyzes the communication strategies of Islamic Religious Education teachers in Islamic parenting education for parents at SMP TAQ Al Hamidiyyah Batealit. A qualitative case study method was employed with data collection techniques through interviews, observation, and documentation. data reduction, data presentation, and drawing conclusions The results identify four main strategies: group communication (majelis taklim), interpersonal communication (counseling), utilization of digital media, and behavioral exemplification (uswah hasanah). These strategies proved effective in creating school-family synergy and enhancing parental understanding, despite challenges of background heterogeneity. The research concludes by emphasizing the importance of an integrated multi-method approach for successful parenting programs. Recommendations focus on developing structured modules and optimizing more interactive communication channels.